Utilization of Vegetable Waste as Alternative Feed Immune Enhancer and Broiler Weight - Sasmita, Farra; Umrawati L, Wa Ode; Amin, Haidir; Oge, La; Harudin, La; Harianti; Tao, Haerudin; Purwanti, Bea (Jurnal Pengabdian Masyarakat Bestari, 2024)
Tobeu Village is one of the villages in Unaaha District, Konawe Regency which has a very potential area for developing livestock businesses, specifically free-range chicken and broiler chicken farming businesses. The Saprin livestock group is one of the livestock groups engaged in the broiler chicken farming business in Unaaha Regency. The service aims to provide education to partners in increasing the weight and immunity of broilers in order to support increased broiler chicken yields by utilizing vegetable waste during October-November 2023. The method in this service consists of physical and non-physical activities as a medium for transferring knowledge and technology to partner groups and physical activities are carried out through technical guidance with a participatory approach. The results of the service provide knowledge and skills in making chicken feed from vegetable waste.